2009
DOI: 10.1136/jech.2009.091496
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status and risk of car crash injury, independent of place of residence and driving exposure: results from the DRIVE Study

Abstract: The higher risk of crash-related hospitalisation for young drivers from low SES areas is independent of driving exposure and rural-urban differences. This finding may help improve and better target interventions for youth of low SES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 40 publications
4
31
0
1
Order By: Relevance
“…Lastly, members of households with income of $50,000 or less (indicated by the LOWINCOME variable) are estimated to have 70 percent higher crash rates, as passengers, than those in households making over $50,000 a year. This result is consistent with findings by Chen et al (41), who concluded that drivers from lower socioeconomic areas face higher crash rates, as compared to drivers from higher status areas, after controlling for driving exposure and population density.…”
Section: Passenger Crash Propensitysupporting
confidence: 92%
“…Lastly, members of households with income of $50,000 or less (indicated by the LOWINCOME variable) are estimated to have 70 percent higher crash rates, as passengers, than those in households making over $50,000 a year. This result is consistent with findings by Chen et al (41), who concluded that drivers from lower socioeconomic areas face higher crash rates, as compared to drivers from higher status areas, after controlling for driving exposure and population density.…”
Section: Passenger Crash Propensitysupporting
confidence: 92%
“…Younger drivers are likely to be inexperienced in negotiating curves (Chen et al, 2010) as they are still novice drivers and coupled with poorer hazard perception skills, increased sensation-seeking propensity, and susceptibility to negative peer influence and risky decision making are at greater risk of crashing on road curves (Scott-Parker et al, 2009). Drivers may also under-or overestimate the sharpness of the curve and fail to safely negotiate the road curve.…”
Section: Contributing Factorsmentioning
confidence: 96%
“…The study sample's demographics and distribution of hypothesized risk factors for crash by level of psychological distress are presented in Table 1. Of the total sample, 5,822 (29%) reported low or no psychological distress (Kessler 10 score, 10-15), 7,664 (38 %) reported a moderate amount of distress (Kessler 10 score, 16-21), 4,992 (25%) reported high distress (Kessler 10 score, [22][23][24][25][26][27][28][29], and 1,535 (8%) reported very high distress (Kessler 10 score, 30-50). More females reported higher levels of distress than males.…”
Section: Resultsmentioning
confidence: 99%
“…The baseline survey asked participants about their psychological distress as well as other factors previously demonstrated to be risk factors for crash. Information on demographic factors was collected: age, sex, Australian Standard Geographic Classification for remoteness [22], and the Australian Bureau of Statistics Index for socio-economic status [23]. Information on exposure to driving and driver training were adapted from the Western Australian Young Driver Cohort Study [24] and the University of Otago Young Driver Pilot Study [25].…”
Section: Methodsmentioning
confidence: 99%